John Gaw Meem at Acoma : The Restoration of San Esteban del Rey Mission - Wingert-Playdon, Kate, 1960- (Book collections on Project MUSE., 2012)
"Built by Spanish Franciscan missionaries in the seventeenth century, the magnificent mission church at Acoma Pueblo in west-central New Mexico is the oldest and largest intact adobe structure in North America. But in the 1920s, in danger of becoming a ruin, the building was restored in a cooperative effort among Acoma Pueblo, which owned the structure, and other interested parties. Kate Wingert-Playdon's narrative of the restoration and the process behind it is the only detailed account of this milestone example of historic preservation, in which New Mexico's most famous architect, John Gaw Meem, played a major role."--